Syarat Sehat Jasmani Sebagai Diskriminasi Tenaga Kerja Difabel - Gaol, Heru Saputra Lumban (INKLUSI, 2020)
The inclusion of the ’physically healthy’ requirement in recruiting job vacancies has led to various interpretations. This practice has been going on for a long time and often violates persons with disabilities' rights to obtain equal employment opportunities. This study aims to analyze the interpretation of physical health requirements in the recruitment of job vacancies. Sources of research data are employers, disabled workers, and the Yogyakarta Provincial Government. Researchers analyzed legal norms and qualitative data, then presented descriptively. The study concluded that there had not been one interpretation from the employer, disabled workers, and the government about ‘being physically healthy.’ The term is often interpreted as ‘being physically complete.’ This biased interpretation discriminates against disabled workers entering the workforce. [Keberadaan syarat ‘sehat jasmani’ dalam rekrutmen lowongan kerja menimbulkan berbagai penafsiran, khususnya bagi tenaga kerja difabel. Praktik ini sudah berlangsung lama dan melanggar hak difabel untuk memperoleh kesempatan yang setara dalam lapangan pekerjaan. Penelitian ini bertujuan menganalisis penafsiran syarat sehat jasmani dalam rekrutmen lowongan kerja. Sumber data penelitian adalah pihak pemberi kerja, tenaga kerja difabel, dan Pemerintah Provinsi Yogyakarta. Penelitian dilakukan dengan menganalisis norma hukum dan data kualitatif, kemudian disajikan secara deskriptif. Penelitian menyimpulkan bahwa belum ada kesatuan penafsiran dari pihak pemberi kerja, tenaga kerja difabel, dan pemerintah tentang kriteria sehat jasmani. Syarat sehat jasmani sering diartikan sebagai fisik yang lengkap. Hal mendiskriminasi tenaga kerja difabel dalam memasuki lapangan pekerjaan.]